Impact of leadership styles on employees' attitude towards their leader and performance: Empirical evidence from Pakistani banks - Muhammad Asrar-ul-Haq; K. Peter Kuchinke (Future Business Journal, 2016)
This paper reports the findings of a study examining the impact of managers' leadership styles on subordinates' performance. The impact of leadership styles on employee performance outcomes is explored theoretically and tested empirically in the Pakistani banking sector. The sample of the study consisted of 224 full-time employees in the banking sector of Pakistan. Findings of this study reveal that there exists a significant relationship between transformational leadership and employee performance outcomes. However, laissez-faire leadership style showed negative relationship with employee performance outcomes in terms of effectiveness, and employee satisfaction. Banking industry in Pakistan is prone to numerous challenges including employee turnover. Model presented in the study will be helpful for the human resource managers and top management to design effective leadership development programs. HRD department can be established and HRD professionals can be hired to assist the managers in organizing training and development programs. Further, it may help to design strategies to satisfy, retain and motivate the employees. Also, it will help the managers decide, which leadership style they should choose in terms of outcomes.
Keywords: 650; Banking; Pakistan; Performance; Transactional leadership; Transformational leadership